2010
DOI: 10.1016/j.physleta.2010.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Period-doubling cascades of canards from the extended Bonhoeffer–van der Pol oscillator

Abstract: This letter investigates the period-doubling cascades of canards, generated in the extended Bonhoeffer-van der Pol oscillator. Canards appear by Andronov Hopf bifurcations (AHBs) and it is confirmed that these AHBs are always supercritical in our system. The cascades of period-doubling bifurcation are followed by mixed-mode oscillations. The detailed two-parameter bifurcation diagrams are derived, and it is clarified that the period-doubling bifurcations arise from a narrow parameter value range at which the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 18 publications
3
25
0
Order By: Relevance
“…An exception is an interesting work published recently in this journal by Sekikawa et al [23]. Among other things, these authors reported two-parameter bifurcation diagrams of the period-doubling bifurcations associated with canards [24] in an extended Bonhoeffervan der Pol (BVP) oscillator shown schematically in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…An exception is an interesting work published recently in this journal by Sekikawa et al [23]. Among other things, these authors reported two-parameter bifurcation diagrams of the period-doubling bifurcations associated with canards [24] in an extended Bonhoeffervan der Pol (BVP) oscillator shown schematically in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The multi-scroll chaotic attractors exhibited by electric circuits have received considerable attention of the researchers theoretically as well as experimentally [23]. The three-dimensional BVP [23] is one of the elec-1 C tric circuits, which realizes chaos and shows very rich, complex dynamic behavior and yet has potential applications. An extended BVP oscillator can show a stable oscillator as well as a stable threshold phenomenon [23].…”
Section: The Extended Bonhoeffer Van-der Pol Chaotic Oscillatormentioning
confidence: 99%
“…The three-dimensional BVP [23] is one of the elec-1 C tric circuits, which realizes chaos and shows very rich, complex dynamic behavior and yet has potential applications. An extended BVP oscillator can show a stable oscillator as well as a stable threshold phenomenon [23]. The extended BVP oscillator has been observed numerically and experimentally in certain systems and has attributes of great utility to medicine, chemical kinetics, neuroscience, electrical circuits and secure communications [15], [23][24][25].…”
Section: The Extended Bonhoeffer Van-der Pol Chaotic Oscillatormentioning
confidence: 99%
See 1 more Smart Citation
“…Since the dynamics near such a quasi-threshold are unstable and expanding, canards produce a chaotic behavior if they are forced even by very small signals [8]. The so-called mixed mode oscillations (MMOs) [9][10][11] are intensively related to canards.…”
Section: Introductionmentioning
confidence: 99%